KAJIAN DAMPAK EMISI UDARA PADA PRODUKSI MINYAK BUMI DI PERUSAHAAN “A” MENGGUNAKAN METODE LIFE CYCLE ASSESSMENT (LCA) - AM, Annur Yudha; Assomadi, Abdu Fadli (Department of Environmental Engineering-Faculty of Civil, Planning, and Geo Engineering. Institut Teknologi Sepuluh Nopember, Surabaya, 2022)
The largest emission from the petroleum production process is dominated by nitrogen oxide (NOx) gas which accounts for 60% of the total emissions. In this research, an assessment of the impacts that occur from petroleum production activities is carried out using the Life Cycle Assessment (LCA) method. In this study, the identification of environmental impacts was carried out using the SimaPro 9 application software and the midpoint-based assessment. In the midpoint assessment, 1 method is used, namely the CML-IA Baseline method. Life cycle impact assessment (LCIA) or impact assessment using midpoint assessment includes global warming, human toxicity, photochemichal oxidation, ozone layer depletion, acidification, eutrophication, abiotic depletion, and abiotic depletion (fossil fuel). Emissions analyzed include CO2, CH4, NOx and SOx. In this study, the scope of analysis used from the process system is cradle to gate. The results of the analysis resulted in the greatest impact value coming from unit A power generator. The largest impact category from the CML-IA Baseline method is acidification. The results of the sensitivity check analysis resulted in the value of both variations above 10%, namely 16% of each variation. The recommended alternative program scenario is cogeneration technology and nonselective catalytic reduction (NSCR) because it can reduce acidification by 69.81%, eutrophication 69.82% and human toxicity 69.40%.